Prolonged Survival of Neutrophils Induced by Tumor‐Derived G‐CSF/GM‐CSF Promotes Immunosuppression and Progression in Laryngeal Squamous Cell Carcinoma - Xiaoke Zhu; Yu Heng; Jingyu Ma; Duo Zhang; Di Tang; Yangyang Ji; Changding He; Hanqing Lin; Xuping Ding; Jian Zhou; Lei Tao; Liming Lu (Advanced Science)
Abstract Tumor‐associated neutrophils (TANs) play a crucial role in tumor progression and exhibit prolonged survival. However, the mechanism underlying their extended lifespan and significance in laryngeal squamous cell carcinoma (LSCC) remains unclear. Herein, it is observed that apoptosis of TANs is significantly delayed owing to induction by tumor‐derived G‐CSF and GM‐CSF through the activation of the PI3K‐AKT signaling pathway, upregulation of anti‐apoptotic Mcl‐1 expression, and downregulation of activated Caspase‐3 levels. It is found that prolonged survival of TANs leads to the accumulation of aged CXCR4+ neutrophils that exhibit potent immunosuppressive properties and are associated with poor patient prognosis. Furthermore, extended survival promotes the enhanced immunosuppressive function of CD8+ T cells by TANs, thereby facilitating the in vitro and in vivo progression and growth of human LSCC tumors. Importantly, this effect could be reversed by blocking G‐CSF and GM‐CSF stimulation of neutrophils. These findings elucidate the pivotal role of pathologically prolonged neutrophil survival in impairing CD8+ T cell immunity and suggest targeting it as a potential therapeutic strategy for tumors.